The Culinary Gender Binary in an Era of Multiculturalism: Foodwork in Toronto’s Late Postwar Italian Immigrant Community - Lallani, Shayan S. (Université d'Ottawa | University of Ottawa, 2018)
This article uses oral histories to examine how migration affected the gender dynamics of foodwork carried out by late postwar Italian immigrants in Toronto. Culinary gender roles remained preserved as narrators journeyed to Toronto. However, by the twenty-first century when national discourse emphasized a multicultural Canada—the climax of the shift toward culinary pluralism—the narrators each embodied a range of food masculinities and femininities. They also described other motives to do partake in culinary labor that cannot be categorized by the traditional binary. A new paradigm that accounts for the experiences of migrants encountering the homogenizing forces of multiculturalism is needed.
Keywords: Immigration; Gender; Urban history; Culinary gender binar; Multiculturalism; Assimilation; Pluralism; Food labor; Italian foodways